2016
DOI: 10.1371/journal.pone.0161058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Staphylococcus aureus Eradication Therapy in Vascular Surgery

Abstract: IntroductionSurgical site infections (SSI) are a serious complication in vascular surgery which may lead to severe morbidity and mortality. Staphylococcus aureus nasal carriage is associated with increased risk for development of SSIs in central vascular surgery. The risk for SSI can be reduced by perioperative eradication of S. aureus carriage in cardiothoracic and orthopedic surgery. This study analyzes the relation between S. aureus eradication therapy and SSI in a vascular surgery population.MethodsA prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, in a randomized, multicenter clinical trial, Bode et al [ 32 ] found that the risk of healthcare-associated S. aureus infections was reduced by almost 60% among patients with decolonization. Similarly, Langenberg et al [ 33 ] confirmed a reduction in SSI with S. aureus decolonization among patients undergoing central vascular reconstruction surgery. The reported S. aureus SSI rate was 13.0% in the positive not-treated group, and 0.0% in the positive treated group.…”
Section: Discussionmentioning
confidence: 87%
“…For example, in a randomized, multicenter clinical trial, Bode et al [ 32 ] found that the risk of healthcare-associated S. aureus infections was reduced by almost 60% among patients with decolonization. Similarly, Langenberg et al [ 33 ] confirmed a reduction in SSI with S. aureus decolonization among patients undergoing central vascular reconstruction surgery. The reported S. aureus SSI rate was 13.0% in the positive not-treated group, and 0.0% in the positive treated group.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies show that a reduction in S aureus -infections might be accomplished in open aortoiliac surgery by means of specific eradication therapy for nasal carriers, which was associated with a significant reduction in 1-year mortality. 19,28 Graft infection with S aureus occurs in less than 1% of aortic grafts and in 2% to 5% of inguinal grafts, with associated mortality and major amputations as high as 40%. It seems that especially in patients with aortoiliac occlusive disease, a large amount of S aureus –related mortality and morbidity can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…From February 2013 onward, a protocol for Staphylococcus aureus nasal screening was used in the research hospital. 19 Following this protocol, all patients were subjected to nasal screening before vascular surgery. Patients who tested positive for S aureus were subsequently treated with eradication therapy consisting of mupirocin ointment and chlorhexidine gluconate soap for 5 days before undergoing surgery.…”
Section: Methodsmentioning
confidence: 99%